Pelatihan Internet Sebagai Media Informasi dan Komunikasi Untuk Meningkatkan Skill Keperawatan Siswa SMK - Agustina Srirahayu; Kresna Agung Yudhianto (Duta Abdimas, 2023)
Citra Medika Sukoharjo Health Vocational School students live far from urban areas and the lack of attention from the local government in conducting outreach, guidance and internet training has made many students, especially those living in rural areas, less aware of the importance of using the internet in a positive way. Internet training as a medium of information and communication to improve nursing skills to be able to maximize the function of healthy information for good communication facilities. The development of technology, especially the internet has brought many changes. Thanks to the help of the internet, all work becomes light. Therefore training and guidance activities in the use of the internet really need to be done to remind and provide awareness for students how to use the internet in a wise way so that in the future their academic abilities and knowledge of the world of education and information will increase. This training will be explained in the form of a presentation using power point. The implementation of this training and guidance is expected that nursing students, especially at this school, are able to use the internet wisely and prudently in order to support efforts to develop civilized human resources who have the ability to compete globally, not only able to compete intellectually but also have good manners and behavior.